KOLEK AS A TRADITIONAL BOAT OF NATUNA PEOPLE - Destriyadi Destriyadi (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
Natuna society in the maritime region has a close relationship with traditional technology in the form of kolek boats. As a material object, kolek is considered an important part of fishing activities since ancient times. The description of kolek is currently still lacking and even very minimally known. This article aims to describe kolek as a traditional technology of Natuna society. Likewise, some traditional boats in Natuna. The formal object of this research is cultural anthropology, while the material object is kolek boats. This descriptive qualitative research uses data collection techniques of observation, direct interview, and literature study. There are three stages of data analysis, namely data collection, data interpretation, and data inference. The traditional technology of kolek boats is not only a means of fishing at sea, but many cultural values. Kolek also holds traditional knowledge that must be preserved.